Bank-Specific, Macroeconomic, and Institutional Factors Explaining the Capital Buffer and Risk Adjustments in Banks: A Simultaneous Approach. Issue 2 (4th March 2021) - Antoun, Roger; Coskun, Ali; Youssef, Darin
ABSTRACT: This study aims to shed light on the capital buffer and risk adjustments in the banking sector of South-Eastern European countries following the financial crisis of 2008 that triggered a series of bank reforms and new regulations. Using Bankscope data for the period 2009–2014, we investigate the effect of economic growth and institutional quality on banks' voluntary capital buffers and risk. Our main findings suggest first that changes in risk positively affect capital buffers. Second, we find that risk adjustments are negatively affected by economic growth, but no significant effect of economic growth on the capital buffer was noted. Finally, our results show that a rise in institutional quality reduces the need for banks to extend their capital buffers.